Biodiversity of lactic acid bacteria and preserving by freeze and spray drying of Lactobacillus plantarum from Marajó cheese - Ferreira, Andreza Angélica (2016)
Northern Brazil, in the Amazon region stands out in the production of an artisanal cheese on the Marajó Island (Pará, Brazil). It is defined as a fresh cheese obtained through natural coagulation of raw buffalo milk by the autochthonous microbiota and subsequent curd fusion. LAB from artisanal cheeses contribute to original sensory properties in these cheeses, characterizing unique and specific products of each region, preserving a tradition of cultural, economic and social importance. Thus, the knowledge of LAB diversity is fundamental to the characterization of this type of cheese. In this context, the aim of this thesis was to isolate and to identify the LAB biodiversity involved in the production of Marajó cheese and to evaluate the effects of freeze drying and spray drying in the preservation of LAB. Preliminary characterization as Gram positive cocci and/or bacilli and as negative catalase plus identification by using 16S rDNA sequence analysis and Rep-PCR were undertaken for 149 LAB isolates obtained from samples of raw buffalo milk, curd and utensils involved in Marajó Cheese making and 97 LAB cocci from Marajó Cheese. Eight species have been identified as follows: Weissella confusa, Streptococcus infantarius, Lactococcus lactis, Leuconostoc pseudomesenteroides, Weissella paramesenteroides, Pediococcus pentosaceus, Pediococcus acidilactici, Lactobacillus brevis and the Enterococcus genus. The Rep-PCR was able to identify different genetic profile showing a high diversity among the evaluated isolates. Among the isolates, the species Lactobacillus plantarum and Lactobacillus paraplantarum were also identified coming from Marajó cheese. And a strain of L. plantarum was selected for preservation of freeze drying and spray drying.The cells of L. plantarum subject to spray drying process at approximately 10 9 CFU.g -1 , while the freeze dried samples showed 10 7 CFU.g -1 after 60 days of storage at 4°C and 20 °C. The spray drying was less damaging than freeze drying for L. plantarum cells. The phenotypic characteristics showed by LAB isolated in this study allow of directing further investigations to preserve LAB strains involved in production of Marajó cheese in order to produce starter and adjunct cultures by spray drying with a high number of viable cells to be used for industrial application through a cost-effective method.